PELATIHAN KONSEP MATEMATIKA KEKONGRUENAN DAN KESEBANGUNAN MENGGUNAKAN PENDEKATAN ETNOBRA DI SMPN 3 CIKANDE - Hamidah, Hamidah; Kusuma, Jaka Wijaya; Auliana, Sigit (Jurnal Ilmiah Pengabdian Kepada Masyarakat, 2023)
Training on mathematical concepts on congruence and equality using ethnomathematics and Geogebra approaches at SMPN 3 Cikande aims to increase students' understanding of complex mathematical materials and relate them to local cultural contexts. In this training, students are equipped with an understanding of mathematical concepts through an ethnomathematical approach that connects mathematical concepts with their daily lives. In addition, the use of Geogebra as a learning aid provides an immersive visual and interactive experience in understanding mathematical concepts. The results of the training showed an increase in students' understanding of mathematical concepts, mathematical thinking skills, and learning motivation. The training also highlighted the importance of developing a mathematics curriculum that is responsive to the student's context and improving teachers' skills in applying innovative learning approaches. Thus, this training not only provides direct benefits for students at SMPN 3 Cikande, but also provides guidance for the development of more effective and relevant mathematics learning in other schools